Investigating Gram-negative bacilli isolates’ sensitivity to ceftazidime/avibactam - Sunali; Mithilesh Kumar Jha; Mukesh Kumar; Maneesh Kumar; Nishant Ranjan (Journal of Family Medicine and Primary Care)
Background: Multidrug resistant (MDR) Gram negative organisms are becoming increasingly common. Carbapenem resistant Enterobacterales (CRE) pose a major threat and necessitate the development of new antibiotics. MDR and carbapenem resistant infections, which are common in intensive care units and hospitals, lead to increased morbidity, mortality, prolonged hospital stays, and higher healthcare costs. New antimicrobials such as ceftazidime avibactam offer potential alternatives to conventional treatments such as tigecycline and colistin, which have significant side effects and limitations. Aim: This study focuses on the antibiotic susceptibility of ceftazidime/ avibactam to Gram negative bacilli found in a large number of clinical samples collected from a tertiary care facility in Netaji Subhas Medical University and Hospital, Bihta, India. Methodology: The study included 81 Gram negative bacteria isolated from patient samples. Based on the Clinical Laboratory Standards Institute guidelines mentioned in the Kirby Bauer disc diffusion method. Result and Conclusion: the results showed that ceftazidime avibactam inhibited 89.9% of the Enterobacteriaceae isolates, which was higher than the 80.3% of amikacin and the 85.1% of meropenem. Ceftazidime avibactam was effective against CRE isolates in 69.9% of cases and against MDR isolates in urine in 94% of cases, which was higher than the 40% of ceftriaxone and 94% of nitrofurantoin. The results show that ceftazidime avibactam can cure MDR and CRE infections, especially urinary tract infections, better than conventional antibiotics, which is a great help in the fight against increasing antibiotic resistance.